The Effect of Job Satisfaction and Compensation on Employee Work Discipline PT. Agung Jaya Bersama Tasikmalaya - Mohammad Rizal Fadhilah; Arga Sutrisna; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of job satisfaction and compensation on work discipline of employees of PT. Agung Jaya Bersama Tasikmalaya. The method used is a quantitative approach with a sample of 34 respondents from employees of PT. Agung Jaya Bersama Tasikmalaya. The data used are primary data and secondary data. The analytical tool used is path analysis using SPSS version 25. The results show that job satisfaction has a direct effect on work discipline. Compensation has no significant effect on Employee Work Discipline and Job Satisfaction has an effect on Work Discipline Through Compensation.